PEMANFAATAN LIMBAH ORGANIK SEBAGAI BAHAN BAKU PUPUK KOMPOS DAN BOKASHI MELAUI PROGRAM KKN-PMD UNRAM 2024 STUDI KASUS DI KELURAHAN DODU - Pratama, Much. Dede; Aziz, M Winky; Ernawati, Ernawati; Kurnia, Triya; Wardiani, Nazmi; Hermawan, Muh. Raka; Ramadhani, Suci Elfira; Amalyah, Sari Nur; Sansan, Julia; Anshari, Buan; Aziz, M. Winky (Universitas Mataram, 2024)
The Community Service Program (KKN) at Universitas Mataram in 2024 was implemented in Kelurahan Dodu, Kota Bima, Nusa Tenggara Barat (NTB), focusing on improving the management of organic waste from agriculture and livestock. This area, while rich in resources, faced challenges in waste management, leading to environmental issues. The program aimed to educate and train the community in producing compost and bokashi fertilizers from organic waste. Methods included socialization, practical training, and ongoing monitoring and evaluation. The training effectively increased community engagement and skill development in waste management, with positive feedback and readiness to continue these practices independently. This initiative has successfully fostered sustainable agricultural practices and strengthened the partnership between the university and the local community.